Numerical analysis of blast pressure parameters for the plant and wall as barrier - Nur Syahirah, Basri Shaff (2019)
Plant is widely planted in many areas mainly to prevent soil erosion and as shading purpose from storm and heavy rain. Nowadays, planting plant is more likely to plant for aesthetical purpose in which the plant is cut to shapes to beautify a place. Previously, there was a research carried out that investigated plant as barrier when subjected to blast load. However, there are only few researches on plant academically published regarding plant as barrier. Thus, the academic reading on plant as barrier is basically limited. The published experiment and accessible for reference of this present study is the work focusses on different objects that is experimented for its ability to absorb or reduce blast pressure. It aims to study the blast pressure parameters of 30 lbs. (13.61 kg) Trinitrotoluene (TNT). Thus, further investigation is required for both RC wall and plant subjected to blast load especially on the appropriate and accurate meshing dependency in AUTODYN. Present work aims to study the blast pressure parameter of 30 lbs. (13.61 kg) Trinitrotoluene (TNT). The AUTODYN non-linear finite element (FE) analysis is commercial software used to develop a validated numerical according to the recorded blast pressure data from previous experiment. Numerical simulation for blast pressure analysis is conducted on four cases of different object barrier. The present numerical study involved cases at open space without any objects acting as barrier, only RC wall acting as barrier, only plant of general type acting as barrier and both plant and RC wall acting as barrier. These four cases are modeled in ANSYS-workbench and simulated in AUTODYN. The numerical results obtained are followed by a validated results reported by previous researches for validation. The present study established that, numerical case with only plant as barrier showed the highest blast pressure reduction by 9.8% and 6.7% compared to cases with RC wall and both RC wall and plant respectively. This might due to the plant that absorbs the blast pressure causing the blast pressure to be significantly reduced to 290 kPa whilst Case 2 and Case 4 reduced to only 490 kPa and 310 kPa respectively. Cases with RC wall present showed the lowest pressure reduction as the pressure reflects the wall surface when the wave hits. The reflection of the blast wave had caused the blast pressure to be magnified. Further investigation is recommended especially on meshing precision for both RC wall and plant as barrier when subjected to blast load.